Periarteriolar niches become inflamed in aging bone marrow, remodeling the stromal microenvironment and depleting lymphoid progenitors - Liming Du; Maria Angelica Freitas-Cortez; Jingzhu Zhang; Yuanyuan Xue; Reshma T. Veettil; Zhiyu Zhao; Sean J. Morrison (Proceedings of the National Academy of Sciences, 2025)
In early postnatal and young adult bone marrow, Leptin receptor–expressing (LepR + ) stromal cells and endothelial cells synthesize factors required for hematopoietic stem cell (HSC) maintenance, including Stem Cell Factor (SCF) and Cxcl12. However, little is known about how these stromal cells change during aging. We performed single-cell RNA sequencing of mouse bone marrow stromal cells at 2, 12, and 24 mo of age. We identified five transcriptionally distinct subsets of LepR + cells, all of which expressed the highest levels of Scf and Cxcl12 in bone marrow throughout adult life. In aging bone marrow, SCF from LepR + cells, but not endothelial cells, continued to be necessary for the maintenance of HSCs and early restricted progenitors. However, arteriolar endothelial cells and other periarteriolar cells expressed increasing levels of interferon during aging. This increased the numbers of periarteriolar Sca1 + Cxcl9 + LepR + cells with an inflammatory gene signature and depleted lymphoid progenitors, at least some of which are also periarteriolar. The periarteriolar environment thus became particularly inflamed during aging, remodeling the stromal microenvironment and depleting lymphoid progenitors in an interferon-dependent manner.